Silica Nanoparticles Disclose a Detailed Neurodegeneration Profile throughout the Life Span of a Model Organism - Annette Limke; Gereon Poschmann; Kai Stühler; Patrick Petzsch; Thorsten Wachtmeister; Anna von Mikecz (MDPI AG, 2024)
The incidence of age-related neurodegenerative diseases is rising globally. However, the temporal sequence of neurodegeneration throughout adult life is poorly understood. To identify the starting points and schedule of neurodegenerative events, serotonergic and dopaminergic neurons were monitored in the model organism C. elegans, which has a life span of 2-3 weeks. Neural morphology was examined from young to old nematodes that were exposed to silica nanoparticles. Young nematodes showed phenotypes such as dendritic beading of serotonergic and dopaminergic neurons that are normally not seen until late life. During aging, neurodegeneration spreads from specifically susceptible ADF and PDE neurons in young C. elegans to other more resilient neurons, such as dopaminergic CEP in middle-aged worms. Investigation of neurodegenerative hallmarks and animal behavior revealed a temporal correlation with the acceleration of neuromuscular defects, such as internal hatch in 2-day-old C. elegans. Transcriptomics and proteomics of young worms exposed to nano silica showed a change in gene expression concerning the gene ontology groups serotonergic and dopaminergic signaling as well as neuropeptide signaling. Consistent with this, reporter strains for nlp-3, nlp-14 and nlp-21 confirmed premature degeneration of the serotonergic neuron HSN and other neurons in young C. elegans. The results identify young nematodes as a vulnerable age group for nano silica-induced neural defects with a significantly reduced health span. Neurodegeneration of specific neurons impairs signaling by classical neurotransmitters as well as neuropeptides and compromises related neuromuscular behaviors in critical phases of life, such as the reproductive phase.